ACE study jako istotny drogowskaz dla kierunku działań edukacyjnych i profilaktycznych w systemie oświaty - Tomkowiak, Hubert (Wydawnictwo Naukowe EDUsfera. Ewa Jurczyk-Romanowska, 2021)
The significance of adverse childhood experiences (ACE) study is multidimensional. First of all, they showed the unprecedented prevalence of adverse childhood experiences in American society. Secondly, they proved how serious the health consequences are associated with it, not only of a psychological nature. Awareness of both of these facts shoul dhave a significant impact on the functioning of the education, upbringing, and prevention systems. The Polish school does not seem to notice this, although we have similar studies carried out in our country, the results of which are also alarming. The article makes a comparison of the results of both studies in order to demonstrate the need to take into account the facts they provide in the construction of the education system, paying much more attention to issues related to upbringing and prevention, also understood in purely medical terms.
Keywords: ACE study; adverse childhood experiences; abused child; education system; prevention